212k views
4 votes
Can you find x for the following equation?
7x+12=3(5x-12)

User Clarenswd
by
4.7k points

2 Answers

0 votes

7x + 12 = 3(5x - 12)

Step 1: Distribute the 3 to the numbers in the parentheses (5x and -12)

7x + 12 = (3 × 5x) + (3 × (-12))

7x + 12 = 15x + (-36)

Step 2: Combine like terms

x's go with x's (7x and 15x)

Subtract 7x to both sides

(7x - 7x) + 12 = (15x - 7x) + (-36)

(0) + 12 = 8x - 36

12 = 8x - 36

Normal numbers go with normal numbers

Add 36 to both sides

12 + 36 = 8x + (-36 + 36)

48 = 8x

Step 3: Isolate x by dividing 8 to both sides

48/8 = 8x/8

6 = x

Hope this helped!

User Bladimir
by
4.8k points
5 votes

Answer:

x = 6

Explanation:

Eliminate parentheses using the distributive property.

7x +12 = 15x -36

You have x-terms and constants on both sides of the equal sign. One way to approach this is to find the x-term with the least coefficient (it is 7x) and subtract everything on that side of the equation.

(7x +12) -(7x +12) = (15x -36) -(7x +12)

Simplify, also known as "collect terms."

0 = 8x -48

Now, divide by the coefficient of x: 8.

0 = x -6

Add the opposite of the constant: 6.

6 = x

__

Alternate solution

By looking for the x-term with the smallest coefficient, we get a positive result when we subtract that term. If we were to subtract 15x from both sides of the equation, it would be ...

-8x +12 = -36 . . . . . . . with a negative x-coefficient

You can still work the problem this way, but it can introduce errors if you're not careful with signs. To finish this, we would subtract 12 to get the x-term by itself:

-8x = -48

Then we would divide by the x-coefficient, -8.

x = -48/-8 = 6 . . . . . same solution; same number of steps

_____

Whenever you add, subtract, multiply, divide, you do the same thing to both sides of the equation.

User Maturano
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.